Cisplatin and dexamethasone separate and combined effect on nephrotoxic processes in female rats - Zhenya Yavroyan; Anna Grigoryan; Nune Hakobyan; Agapi Hovhannisyan; Tamara Abgaryan; Anna Karapetyan; Emil Gevorgyan (Український Журнал Нефрології та Діалізу)
Nephrotoxicity is one of the most severe side effects caused by cisplatin, limiting its use at high, effective concentrations. Dexamethasone, known for its strong anti-inflammatory and immunomodulating properties, is often used to alleviate cisplatin-induced side effects. However, dexamethasone also exhibits pro-oxidant properties and has been associated with morphological impairments and acute kidney injury. Although the mechanisms of cisplatin-induced nephrotoxicity are complex and involve numerous cellular processes, oxidative stress is widely accepted as the primary cause of this pathology. This study aims to investigate how dexamethasone, despite having effects similar to cisplatin, alleviates the side effects caused by this drug.